PENGETAHUAN DAN MOTIVASI IBU POST SECTIO CAESAREA DALAM MOBILISASI DINI - Nurfitriani Nurfitriani (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2018)
INTRODUCTION Early mobilization is important to be done to accelarate the mothers’s healing after section caesarea in order to be able to do daily activity normally. This mobilation is done depending on whether there is complication of baby delivery or not and post parturition. The post section caesarea mothers are allowed to get up 6 to 10 hours after the baby delivery. The late of early mobilization makes the mothers codition worse and the healing of post section caesarea becomes late. The purpose of this research was to describe the knowledge and the motivation about early mobilization on post section caesarea in RSUD Abdul Manap Kota Jambi Tahun 2016. METHOD This research used descriptive method with accidental sampling as he technique in collecting data. The collected data were analyzed using univaried analysis. The respondents were 34 mothers of section caesarea. This research was done in RSUD Kota Abdul Manap Kota Jambi from 12 July to 13 August 2016. RESULT Of the 34 respondents studied about the knowledge variables, there were 16 (47.1%) respondents with good knowledge, 4 (11.8%) knowledgeable and 14 (41,2%) low knowledge. While 18 (52,9%) respondents have high motivation and as much as 22 (65%) of respondents early mobilization. CONCLUSION AND RECOMENDATION It could be concluded that the mothers were motivated to do early mobilization. Hopefully, the medical assistans can give information about early mobilization to the section caesarea mothers, such as doing extension, giving brochure/leaflet of early mobilization, so that sectio caesarea can accelerate the healing process of post sectio caesarea. Keywords: Knowledge, Motivation and Early Mobilization